Choques macroeconómicos y tipo de cambio real: Alguna evidencia para Argentina - Luis N. Lanteri (Atlantic Review of Economics, 2014)
– Dornbusch's exchange rate overshooting hypothesis (1976) is a central building block in international macroeconomics. This paper analyzes the effects of monetary and other macroeconomic shocks on the real exchange rate in the case of a small economy like Argentina. The paper uses SVAR models with short term restrictions, and quarterly data of this country, covering the period 1993-2014. Results show that a contractionary monetary shock generates an appreciation of the real exchange rate in the short term and then a gradual depreciation of this variable, as the hypothesis of Dornbusch suggests.
Keywords: C32; E52; F31; F41; 330; monetary and other macroeconomic shocks; real exchange rate; SVAR models; Argentina economy